Free and open Indo-Pacific strategy outlook - Arase, David (Trends in Southeast Asia, 2019)
The United States launched a new Free and Open Indo-Pacific (FOIP) strategy in late 2017 after reluctantly concluding that its patient effort to engage and socialize China to the rules-based order since 1972 had failed. China's behaviour since 2009 convinced the United States that China is a revisionist power seeking to impose an authoritarian model of governance in Asia which, if successful, would end the rules-based order in the Indo-Pacific as well as endanger US security and vital trade interests. The new US FOIP strategy initiative seeks to engage like-minded nations in economic, security (both traditional and non-traditional), and political governance partnerships to construct a collaborative and scalable network of relations that will be able to respond flexibly to meet a wide range of stakeholder needs and regional contingencies across the Indo-Pacific region. The United States occupies a peak organizing role in this network and works with a hierarchy of partners distributed throughout the vast Indo-Pacific to meet the economic, security, and governance capacity needs of network members at any level. The rules-based order is the "operating system" of this network approach, and so the network itself sustains the rules-based order for its members as a collective good. FOIP is more like a club that generates rules-based order benefits for its members and as such has little in common with Cold War bloc politics and containment strategy. Bearing in mind that FOIP is only in its start-up phase and is likely to gather momentum going forward; that the elements of this network strategy are already in place; and that the United States and its main FOIP partners together have considerable material, organizational, and soft power resources, one may say that its prospects for long-term sustainability and success are not bad